Analysis of hospital-based healthcare provision for people living with HIV who use drugs in Ontario, Canada: “Beyond my Scope!” - William O’Leary; David J. Brennan; Rachelle Ashcroft; Soo Chan Carusone; Adrian Guta; Carol Strike (Cogent Social Sciences, 2024)
People living with HIV (PLWH) who use drugs are hospitalized at higher rates than the general population and report receiving poor care during hospitalization. The patient experience of PLWH during hospitalization is influenced by the clinical practice of healthcare providers (HPs). However, there is a gap in the literature that articulates the perspectives of HPs who deliver care to this population. Semi-structured interviews were conducted with HPs on in-patient hospital units in Toronto and Ottawa, Canada. Structuration-theory-informed thematic analysis was used to explore the beliefs and rules identified and utilized by HPs that affect healthcare delivery during the hospital stay of PLWH who use drugs. Interviews were audio-recorded and transcribed verbatim. The participants included 26 hospital-based HPs (i.e. Physicians, Registered Nurses, Social Workers, Pharmacists, Dietician, and Nurse Practitioner) who deliver healthcare services to people who are living with HIV and who use drugs during the hospital admission. Most HPs stated that no explicit hospital rules exist to guide their clinical practice when engaging with people who use drugs and many indicate that providing care to this population is beyond their scope of practice. The lack of explicit rules results in implicit rules and actions that may negatively impact the delivery of equitable healthcare for PLWH who use drugs.